A Case of Exertional Rhabdomyolysis: When Exertion Exceeds Capacity. (April 2017) - Jordan, Kathleen S.; Mannle, Sarah E.
Abstract : The purpose of this article is to present a discussion of a young adult patient with exertional rhabdomyolysis. Rhabdomyolysis is the process of muscle tissue destruction and damage to the cell membrane, with subsequent release of the intracellular myocyte contents into the systemic circulation. This leads to the potential for the life-threatening systemic complications of electrolyte abnormalities, cardiac dysrhythmias, acute kidney injury, compartment syndrome, and disseminated intravascular coagulopathy. Rhabdomyolysis as a syndrome can be difficult to recognize and diagnose in the emergency care setting due to the fact that there are many etiologies and variations in symptomatology. The emergency care provider must have an astute knowledge base of this disease process and consider this pathology in the differential diagnosis of any patient at risk to achieve optimum patient outcomes and reduce morbidity and mortality.